LaGa-based bulk metallic glasses - 赵林志 薛荣洁 汪卫华 白海洋 (Chinese physics B, 2017)
We report the formation of La Ga-based bulk metallic glasses. Ternary La–Ga–Cu glassy rods of 2–3 mm in diameter can be easily formed in a wide composition range by the conventional copper mold casting method. With minor addition of extra elements such as Co, Ni, Fe, Nb, Y, and Zr, the critical diameter of the full glassy rods of the La–Ga–Cu matrix can be markedly enhanced to at least 5 mm. The characteristics and properties of these new La Ga-based bulk metallic glasses with excellent glass formation ability and low glass transition temperature are model systems for fundamental issues investigation and could have some potential applications in micromachining field.